Overcurrent Mechanism and Suppression Control for MMC Arms in Hybrid Cascaded HVDC System - Nan Zhang; Xiaodong Li; Zheren Zhang; Zheng Xu (CSEE Journal of Power and Energy Systems)
The hybrid cascaded HVDC system employs a line commutated converter (LCC) as the rectifier and an LCC in series with multiple paralleled modular multilevel converters (MMCs) as the inverter. MMC arms are susceptible to overcurrent following a severe AC fault at the receiving end, however, its fundamental mechanism has not been totally revealed. Therefore, this article explores the overcurrent characteristics on MMC arms, in terms of both the DC and AC components. Apart from the DC overcurrent component induced by the commutation failure (CF) of the inverter LCC, the AC overcurrent component is also significant. It dramatically depends on the coupling effects among the AC systems of the inverter side. Further, corresponding suppression strategies are proposed, which are applicable to different receiving-end AC fault scenarios. Eventually, the time-domain simulation results from PSCAD/EMTDC validate the effectiveness of the proposed overcurrent suppression control. It is also demonstrated that the presented methods can not only suppress overcurrent for MMC arms, but also reduce the imbalanced power between two sides, as well as improve the dynamic performances of the entire system.